Enhancing student engagement and cognitive skills in sociology: A qualitative study of quizizz true/false mode in an Indonesian high school - Afiah, Anisa; Ramadhan, Iwan; Zatalini, Adhalia (STAI Auliaurrasyidin Tembilahan, 2025)
This study examines a student engagement model utilizing the Quizizz True or False mode in Sociology for Class XI IPS 3. Employing a qualitative descriptive approach, primary data were collected through observations and interviews with the Sociology teacher and 10 purposively selected students representing diverse engagement levels and group dynamics. Secondary data included school documents. Data analysis followed stages of collection, reduction, presentation, and conclusion drawing, with validity ensured through prolonged observation, persistence, and triangulation. Findings reveal that engagement implications encompass four behavioral aspects: (1) participation/contribution, (2) collaboration, (3) initiative/independence, and (4) motivation/interest, all enhancing active learning. Cognitive improvements were observed across four domains: knowledge/comprehension, application, analysis, and evaluation. The model demonstrated efficacy, with average scores rising from 86.67 (first session) to 95 (second session), indicating improved learning outcomes. These results underscore the potential of gamified quiz tools to bolster both engagement and academic performance in social science education.